Учет трения при гармоническом нагружении круговой трещины - Меньшиков, А.В.; Гузь, И.А. (Видавничий дім "Академперіодика" НАН України, 2007)
We study the dependence of the stress intensity factors (transverse and longitudinal shear modes) on the magnitude of the friction coefficient for a flat penny-shaped crack under oblique harmonic loading.